2007
DOI: 10.1097/00004010-200701000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of distance to primary care physician on health care utilization and disease burden

Abstract: HMO members consume more health care and had higher disease burden as their distance from their PCPs increased. The distance traveled by the individuals to their PCPs could be incorporated when adjusting managed care financial risk models. Other remedies include negotiating higher capitation rates for distant patients, carving out distant patients from any financial risk model, or excluding such patients from provider performance assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 11 publications
2
27
1
Order By: Relevance
“…This result collaborates findings of researchers from other countries [8][9][10][11] and also previous research in Israel [5,[12][13][14]17,18] devoted to issues of equal health services for the periphery.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result collaborates findings of researchers from other countries [8][9][10][11] and also previous research in Israel [5,[12][13][14]17,18] devoted to issues of equal health services for the periphery.…”
Section: Discussionsupporting
confidence: 90%
“…A later American study by Billi and Pahlinger [10] in the state of Michigan sought to define the maximum distance for effective accessibility; it found that the optimal distance between home and clinic for optimal accessibility was no more than 10 miles (16 km), while distances over 50 km constitutes a serious barrier to the accessibility of healthcare. A Canadian study by Seidel et al [11] that examined the use of a pre-surgery clinic in Alberta Canada found that 66% of the patients living up to 50 km from the clinic opted for this service prior to surgery, compared to 52% living over 50 km from the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that costs and disease burden increase as distance from providers increases (Billi et al 2007;Fortney et al 1999). Distance from providers can mean that patients wait longer to receive needed care, or resort to more costly emergency services because they are without access to less expensive community care as problems arise and begin to worsen.…”
Section: Community Based Services and Geographic Information Systemsmentioning
confidence: 99%
“…Geographical access is an important determinant of treatment utilization in the general population [6]. Substance use treatment services have been criticized for not being easily available and accessible to those in need for such services.…”
Section: Introductionmentioning
confidence: 99%